Virtual Reality and Artificial Intelligence: Challenges and Opportunities in its Implementation in Mathematics Learning - Fiqri, Cindy Indra Amirul; Cholily, Yus Mochamad; Syaifuddin, Mohammad; Effendi, Moh. Mahfud (Jurnal Riset Pendidikan Matematika, 2025)
This study explored the challenges and opportunities of implementing Virtual Reality (VR) and Artificial Intelligence (AI) in mathematics education at secondary schools. While VR and AI offer transformative potential to enhance learning through immersive visualization of abstract concepts (e.g., 3D geometric modeling) and personalized adaptive instruction, their adoption faces barriers such as high costs, inadequate infrastructure, and insufficient teacher training. Nevertheless, stakeholder support from educators and students highlights their capacity to foster interactive and engaging learning environments. A mixed-methods approach combining interviews, questionnaires, and paired t-tests revealed significant improvements in student motivation and mathematical understanding post-VR implementation (t = -176.991, p < 0.001). Recommendations emphasize policy-driven financial support, localized content development, and scalable teacher training programs aligned with global best practices. By addressing systemic challenges, VR and AI can become pivotal tools for advancing equitable and innovative mathematics education.